Pembelajaran Keterampilan Berbicara di Era Abad 21 Berbasis Pendekatan Quantum - Apri Lia; Ubaidillah Ubaidillah (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
Nowadays, speaking skills are one of the language skills to be achieved in modern language teaching, including Arabic. The success of learning is influenced by many factors, one of which is the learning method. This paper aims to determine the concept of learning based on a quantum approach and methods of learning speaking skills based on a quantum approach. This paper is a type of literature research with a descriptive qualitative approach. The data sources used were books and journal articles related to the research, then the data were analyzed using content analysis techniques. This study indicates that learning Arabic speaking skills in this era can use the direct method and the audiolingual method, taking into account the principles of quantum learning. Quantum learning can increase students' motivation and achievement because it is supported by a comfortable and fun learning atmosphere.